2022
DOI: 10.1016/j.radonc.2021.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Whole lung irradiation as a novel treatment for COVID-19: Final results of the prospective randomized trial (WINCOVID trial)

Abstract: Background and Purpose The ability of Low dose radiotherapy (LDRT) to control the unprecedented cytokine release associated with COVID-19 pathogenesis has been an area of widespread research since the COVID pandemic. It has not been studied adequately whether the anti-inflammatory effect of LDRT provides additional benefit when used concurrently with steroids amongst other standard pharmacologic therapy. Material and Methods 51 RT-PCR positive COVID-19 patients were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
(11 reference statements)
0
14
0
4
Order By: Relevance
“…Observations from these studies indicate that Low-dose radiotherapy (LDRT) for Covid-19 pneumonia delivers doses between 0.3 and 1 Gy. LDRT does not decrease the viability of virus directly, but it may increase the effectiveness of antiviral immune responses in the early/medium stages of SARS-CoV‑2 infection [ 141 , 146 , 151 , 164 , 167 , 171 , 177 , 179 ].…”
Section: Resultsmentioning
confidence: 99%
“…Observations from these studies indicate that Low-dose radiotherapy (LDRT) for Covid-19 pneumonia delivers doses between 0.3 and 1 Gy. LDRT does not decrease the viability of virus directly, but it may increase the effectiveness of antiviral immune responses in the early/medium stages of SARS-CoV‑2 infection [ 141 , 146 , 151 , 164 , 167 , 171 , 177 , 179 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many clinical studies have since evaluated the role of LDRT to lungs in COVID-19 pneumonia. Most of them are single arm studies and have documented feasibility, tolerability, and clinical benefit ( 16 , 21 , 22 ). However few studies such as that of Papachristofilou et al.…”
Section: Discussionmentioning
confidence: 99%
“…One study was suspected of having provided incorrect results due to discrepancy between methodological analysis, reported results, and illustrated OS figures and was therefore removed from the meta-analysis 12 ; however, the presented results are discussed separately. Finally, 9 studies (with a total of 151 WLI recipients) were considered eligible to enter the analysis of aggregated 28-day OS rate of patients receiving WLI [17][18][19][20][21][22][23][24][25] (quantitative analysis). Six studies had both intervention and control groups (115 participants in the intervention group and 98 participants as controls).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Six studies had both intervention and control groups (115 participants in the intervention group and 98 participants as controls). 12,17,[20][21][22][23] One of these controlled studies was the excluded study due to erroneously reported results. Eventually, 4 studies were included for meta-analysis of intubation-free days within 15 days after WLI and 5 studies for meta-analysis of OS HR.…”
Section: Study Characteristicsmentioning
confidence: 99%